Presumed Consent Atas Tindakan Medis Berisiko Tinggi Pada Kegawatdaruratan : Perspektif Undang-Undang Nomor 17 Tahun 2023 - Baroto SP, AK Wisnu (Magister Ilmu Hukum - Universitas Hang Tuah, 2023)
Patients are required to provide informed consent before undergoing medical procedures in normal situations, but this does not apply in emergency situations, where presumed consent is used instead. Doctors often face situations that require high-risk medical interventions for emergency patients. The concept of presumed consent for such actions is not recognized under Law Number 17 of 2023 concerning Health. The purpose of this study is to analyze the role of presumed consent in the perspective of this law regarding high-risk medical interventions in emergency cases. This research adopts a normative juridical approach, specifically legal literature research, utilizing legislative and conceptual approaches. The analysis results indicate that presumed consent for high-risk medical interventions in emergency situations is not clearly regulated in Law Number 17 of 2023. However, doctors can still rely on other articles in this law, including Article 293 paragraph (10) emphasizing the best interests of the patient, Article 275 paragraph (1) mandating doctors to provide assistance in emergency cases, and Article 273 paragraph (1) providing legal protection to doctors who act in accordance with standards. Additionally, Article 275 paragraph (1) also exempts doctors from liability in emergency cases, providing legal security for doctors to act swiftly to save lives without hesitation.